An Investigation of the Performance of Due Process Mechanism in the Execution of Construction Projects in Nigeria - Ayangade J. A.; Wahab A.B.; Alake O. (Civil Engineering Dimension, 2009)
Various procurement methods are in use in the award of public contract in Nigeria. The traditional method, which is widely used, has been criticized for its non-performance in projects execution and delivery. To avoid the adverse effects of the current contract procurement methods, Due Process mechanism was introduced. This study, therefore investigated the level of importance of due process by parties involved in the award of public contracts, the performance of Due Process and factors that may affect its functions. The survey was carried out by administering structured questionnaires and interviews on the practitioners in the construction industry that were in the private and public sectors. The data collected were analysed with the use of both descriptive and inferential statistics. The study showed that Due Process has become a new initiative being widely embraced by parties in public contract and has helped in saving public fund by corrupt practices that usually characterize award of contracts. The study also showed that the absence of legal and other institutional frameworks were among the factors that affect the performance of due process in the country.